CORRELATION OF HEAD CIRCUMFERENCE WITH HEIGHT BASED ON SEX IN MONGOLOID RACE AT 18-45 YEARS OLD IN RIAU PROVINCE - Fikri Ruriandy Aufi; Dedi Afandi; Chunin Widyaningsih; Fajri Marindra Siregar (Journal Medical Universitas muhammadiyah Makassar, 2021)
Background:Forensic identification is an important thing to indentify victim.Determine the victim’s height is the best way to facilitate the indentification process,but sometimes the condition of the victim isn’t always intact. Identificator need apredictor bone from the victim to get the height,one of the predictor bone is skull.Skull has a rigid structure, so its expected to be astrong bone and can be a predictorto get the victim’s height.Purpose: This researchwas purpose to determine correlation and linear regressionhead circumference with human height in mongoloid race based on sex at 18-45 yearsold in Riau Province.Method: This research was an analytic study with cross sectionalresearch design.The method uses the accidental sampling method to take subject.The subject wasmongoloid race population at 18-45 years old in Riau Province.This study usedstauture meter and tipeline to measue human height and head circumference. Analysisof this study used a computer software.Result: The total respondents were 226 people (113 men and 113 women) at 18-45years old. The result showed a sicnificant correlation (p0,01) in men, women, andtotal respondents. The correleation in men (r=0,43) and women (r=0,47) respondentsindicate a moderate correlation, meanwhile in total respondents (r=0,61) indicate astrong correlation. The regression formula for men is 102,67 + 1,15 (HeadCircumference) ± 4,71, for women is 94,24 + 1,15 (Head Circumference) ± 4,58 andfor total respondents is 44,81 + 2,12 (Head Circumference) ± 5,96. this result of thisstudy shows that the head circumference has a correlation with body height and it canbe use to determine body height.Conclution: The conclution of this research is there is a positive correlation betweenhead circumference and body height based on sex in mongoloid race at 18-45 years inRiau Province.Keywords : Forensic Identification, Head Circumference, Height, Correlation,Regression Formula.Correspondence should be addressed to Dedi Afandi; Dediafandi4n6@gmail.com.